A Tale of Two Colonies : What Really Happened in Virginia and Bermuda? - Bernhard, Virginia, 1937- (Book collections on Project MUSE., 2011)
In this fascinating tale of England's first two New World colonies, Bernhard links Virginia and Bermuda in a series of unintended consequences resulting from natural disaster, ignorance of native cultures, diplomatic intrigue, and the fateful arrival of the first Africans in both colonies. --from publisher description.